PENDUGAAN UMUR SIMPAN MENGGUNAKAN METODE ACCELERATED SHELF-LIFE TESTING (ASLT) DENGAN PENDEKATAN ARRHENIUS PADA DESTILAT CUKA FERMENTASI HASIL SAMPING CAIRAN PULPA KAKAO - Supariatna, I Gede Rusli; Ganda Putra, G. P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
The atms of this study were (1) to knowing the change of quality characteristics from destilated fermentation vinegar from pulp liquid waste of cocoa beans during storage  dan (2) to determine shelf life of destilated fermentation vinegar from pulp liquid waste of cocoa beans using Accelerated shelf-life testing (ASLT) method with Arrhenius approach . The observed Parameters is temperature. The temperature is 30 °C , 40 °C and 50 °C. The Observed variable is acetic acid content, pH, total dissolved solids and absorbance. The result showed that acetic acid content had the greatest decrease in 50 °C temperature. This shows that acetic acid content are inversely proportional to temperature rise. While the content of pH, total dissolved solids and turbidity experienced the greatest increase in 50 °C temperature. This shows that pH, total dissolved solids and turbidity are proportional to the temperature rise. The results of the calculation showed that at a temperature of 20 °C, 30 °C, 40 °C and 50 °C has a shelf life of 226 days, 167 days, 126 days, 96 days andn 75 days. Keywords : Destilated fermentation vinegar of cocoa,   Accelerated shelf-life testing , Shelf life